Leadership in the Trenches: A Case of Education Leadership in the Philippines - Amante, Helen U (Archīum Ateneo, 2021)
Millions of Filipino school children are enrolled in public elementary and high schools in the Philippines. These schools are unequally resourced in terms of both well-trained teachers and physical facilities and face different forms of challenging circumstances in their respective contexts. Against all odds; however; some of these schools have succeeded in significantly improving student outcomes in terms of performance in the National Achievement Test and other indicators. The leadership of principals and the support they have gained from the community are at the fulcrum of the school improvement and the significant increase in student achievement in these schools. Exemplary principals identify interventions that can bridge gaps of learning and set goals to measure the level of success of interventions. They communicate with parents; teachers and various agencies of the government to help them address student problems and obstructions to their learning. A whole school community approach facilitates the resolutions of problems. However; the stories also tell us that the resolution of problems and achievement of goals often take a long time. These principals made a commitment to see the changes through and to stay with the young for as long as they remained principal in the school. The outstanding principals also showed a firm resolve to see things through despite obstacles. They persevered in the efforts corollary to the long term vision that had for their schools. They harnessed community resources to meet the needs of the school. Interventions rendered by the outstanding school principals included the provision of a feeding program; conversion of spaces for classroom use; efforts to address teacher discipline as well as engaging parents and local government units in the school improvement process. The daunting challenge may also include peace and order conditions that may put the life of the school principal at stake. Steadfastness and firmness in purpose enabled them to achieve their schools' visions despite obstructions and distractions. Leading improvement in schools is a complex task especially when these schools are located in disadvantaged settings. In Philippine public schools where children come from backgrounds of extreme social and economic deprivation and where funding from the government is sorely insufficient the school principal faces very daunting challenges. However; the strong leadership of the school principal and support from the community made it possible for student achievement results to improve; despite the odds..